2020
DOI: 10.1108/jec-04-2020-0072
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship education intention and entrepreneurial intention amongst disadvantaged students: an empirical study

Abstract: Purpose Disadvantaged students face social exclusion and undergo a different treatment than mainstream students. This alters their entrepreneurial intention subsequently. This study aims to investigate the factors affecting disadvantaged students’ intention in their willingness to undergo entrepreneurship education as a vocational course. The variables include self-efficacy, need for achievement (nAch) and family background. The paper further examines whether entrepreneurship education intention enhances their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…Perceived self-efficacy is a measurement of individuals' abilities and skills that can indicate their beliefs and intentions on how they want to perform and achieve (Shrivastava and Acharya, 2020). Perceived self-efficacy has been adopted as a predictor to intentions and performance that enhance EI (Boyd and Vozikis, 1994;Chen et al, 1998).…”
Section: Perceived Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…Perceived self-efficacy is a measurement of individuals' abilities and skills that can indicate their beliefs and intentions on how they want to perform and achieve (Shrivastava and Acharya, 2020). Perceived self-efficacy has been adopted as a predictor to intentions and performance that enhance EI (Boyd and Vozikis, 1994;Chen et al, 1998).…”
Section: Perceived Self-efficacymentioning
confidence: 99%
“…Attitudes towards behaviour, subjective norms, and perceived behavioural control can be adopted to predict intentions to perform behaviours (Ajzen, 1991). This theory has been applied in the studies of entrepreneurship, such as the effect of entrepreneurship education and EI (Shrivastava and Acharya, 2020). Furthermore, intention is a predictor of behaviour and action, such as a self-plan to become an entrepreneur or to start entrepreneurship activities in the future (Lent et al, 1994;Souitaris et al, 2007;Shrivastava and Acharya, 2020).…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…These earlier studies have shown that SN is a weak predictor of EI. However, the study suggests that in collectivistic cultures like India, students may be more susceptible to external influences, such as peer pressure, societal expectations, and guidance from relatives and teachers, when it comes to pursuing entrepreneurship (Shrivastava and Acharya, 2020). This is because Indian culture places a significant emphasis on family, friends, and society in shaping an individual's beliefs and behaviours (Marmat, 2021).…”
Section: Discussion Implication and Conclusionmentioning
confidence: 99%